The use of financial software in economic analysis and business decision-making (REDEL. Revista Granmense de Desarrollo Local, 2025)
The use of technological tools in financial management has become a determining factor in improving the efficiency of economic analysis and the quality of business decisions in competitive environments. The objective of this article is to analyze the influence of financial software on economic analysis and business decision-making, considering its impact on the objectivity, precision, and sustainability of organizational management. The research was conducted using a mixed-methods approach, and the data were processed using descriptive statistics and correlation analysis techniques, which allowed for the identification of a significant relationship between the level of financial software use and the quality of business decisions. The results showed that organizations that systematically use these tools exhibit a higher level of efficiency in economic evaluation, a reduction in financial risk, and more well-founded decision-making compared to those that rely on traditional methods. Additionally, limitations associated with staff training and resistance to organizational change were identified, which affect the full utilization of these technologies. It is concluded that financial software constitutes an indispensable strategic support for economic analysis and business decision-making, provided it is integrated with sound managerial judgment and appropriate organizational processes.
Keywords: financial software; economic analysis; decision-making; business management; financial technology